REKONDISI TRANSFORMATOR UNTUK MENGATASI MENURUNNYA KEMAMPUAN ISOLASI PADA TRANSFORMATOR DISTRIBUSI 20 kV - Nasrul Harun (Jurnal Teknik Elektro, 2016)
Transformer insulator is an important part in electrical devices because it can muffle breakdown voltage and current interference. Refinement of transformer insulator can be done by replacing previous insulator such as recondition of electrical coils resistance and transformer oil. Recondition of transformer should be done in insulator of electrical coil especially if this coil was burned before. This breakage can cause no voltage in one of transfomer phase. Reparation which should be done is substitution of secondary electrical coil and oil transformer